Reduction of social inequalities in life expectancy in a city of Southeastern Brazil - Barros Marilisa BA; Belon Ana Paula (BMC, 2011)
Abstract Background Around the world the life expectancy at birth has risen steadily over time. However, this increase in life years is not equally distributed among different social segments of the population. Studies have demonstrated that social groups living in deprived areas have a shorter life expectancy at birth in comparison to affluent ones. The aim of this study was to evaluate inequalities in life expectancy by socioeconomic strata in a city with one million inhabitants in Southeastern Brazil, in 2000 and 2005. Methods Through an ecological approach, the 49 areas of health care units of the city were classified into three socioeconomic strata, defined according to variables of income and educational level of the heads of household obtained from the 2000 Census. Life tables were constructed by sex for each of the three socioeconomic strata in 2000 and 2005. Results The life expectancy at birth for men and women living in poor areas was 6.9 and 5.5 years lower in comparison to the affluent ones in 2000. Between 2000 and 2005, these social inequalities in life expectancy at birth reduced, since the groups with lower socioeconomic level had gained more life years. The increase in life expectancy at birth experienced by areas with worse living conditions was 3 times higher than the increment estimated for prosperous areas for both sexes. Males had the greatest gain in life years, leading to a narrowing of gender differentials in life expectancy between 2000 and 2005. Conclusions The reduction of social inequalities in life expectancy suggests that living and health conditions have improved over time, due to social and health policies. The expansion of both health care coverage and cash transfer policies could have had positive effects on mortality reduction and on the consequent increase in the life expectancy, especially for the poor population.